The Ponto-Caspian and native amphipod life history in the Daugava River, Latvia - Paidere Jana; Brakovska Aija (Oceanological and Hydrobiological Studies)
Population structure, reproductive parameters and other life history traits are among the main preconditions for alien amphipods’ successful invasion. In the freshwaters of Northern Europe, i.e. Latvia, the overall life history of alien Ponto-Caspian amphipods is little known. Furthermore, the population structure and reproductivity of native Gammarus pulex have not been studied in Latvian freshwaters. The aim of the study was to describe the life history of Gammarus varsoviensis, Pontogammarus robustoides and the coexistent G. pulex. Their population structure, reproductive period and fecundity in the Daugava River were evaluated as part of this study from 2017 to 2019. The results revealed that the reproductive period of G. varsoviensis and P. robustoides lasted from four to five months, with up to three generations per year and a high proportion of juveniles. The average number of eggs for G. varsoviensis was 31 (maximum: 69) and for P. robustoides 28 (maximum: 81), with ovigerous females of both species being an average of 11.3 mm. Gammarus pulex had one generation per year with a high proportion of juveniles. The average number of eggs per brood was 27 (maximum: 41) with the average size of ovigerous females being 10.7 mm.